2012
DOI: 10.5402/2012/675310
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health-Related Quality of Life of Surgically Treated Pituitary Adenoma Patients: A Descriptive Study

Abstract: Context. The literature concerning the health-related quality of life (HRQoL) of patients with surgically treated PA is controversial. Objective. To describe the long-term HRQoL of surgically treated patients in all PA classes. Design and subjects. The 15D, a generic HRQoL instrument producing a 15-dimensional profile and a single 15D index score (a difference ≥0.03 on a 0-1 scale is considered clinically important), was used to assess the HRQoL of a 13-year surgical cohort of PA patients in Northern Finland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
(32 reference statements)
5
20
2
Order By: Relevance
“…It has been reported that patients with pharmaceutical therapy showed decreased QoL scores; however, these studies included a substantial number of patients treated with radiotherapy, which could affect QoL [10,27,37]. In this study, we excluded patients with a history of radiotherapy and showed a decreased QoL in patients with pharmaceutical therapy compared with those with surgery alone, which was in line with the previous report [48].…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that patients with pharmaceutical therapy showed decreased QoL scores; however, these studies included a substantial number of patients treated with radiotherapy, which could affect QoL [10,27,37]. In this study, we excluded patients with a history of radiotherapy and showed a decreased QoL in patients with pharmaceutical therapy compared with those with surgery alone, which was in line with the previous report [48].…”
Section: Discussionsupporting
confidence: 89%
“…The results of the present study demonstrate, as shown previously in patients with acromegaly and in patients with other pituitary adenomas, as well as in other endocrine diseases, that both age and comorbidities are independent predictors of HRQoL. Moreover, the use of the 15D enables indirect comparisons with the previous studies demonstrating impaired HRQoL in Finnish patients with acromegaly and different pituitary adenoma subgroups, as they also used the 15D instrument.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies suggest patients with functional pituitary adenomas (FPAs) to suffer from health‐related quality of life (HRQoL) impairment . Acromegaly and Cushing's disease associate with the most notable impairment of HRQoL . In 2006, Kauppinen‐Mäkelin et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data suggesting an association between hypopituitarism and reduced QoL in CD are mixed based upon several generic and disease‐specific QoL questionnaires . Our study did not observe this finding using the HADS and CushingQoL questionnaires.…”
Section: Discussioncontrasting
confidence: 94%